Islamic Educational Management based Culture in Madrasah Diniyah Zumrotus Salamah Tawangsari – Tulungagung - M. Abdillah Subhin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
The 21st century is the heaviest terrain in the history of development Madrasah Diniyah in some parts of Indonesia, ne of them is Tulungagung and arrounds. In response to the challenges of the times, Madrasah diniyah as an Islamic education organization is expected to strength and develop the Islamic soul as well as a clinic of morality and knowledge. The need for creative and innovative management will evoke the brand image of Madrasah diniyah, which recently experienced a deterioration in terms of children's education. In this era, the entry of western culture into Indonesia is very influential on children's education. This paper discusses the management of Madrasah Diniyah that is culture based. The type of approach used is qualitative descriptive that will provide direct benefits as a source of information to the public.